Unilateral Maxillary Sinus Actinomycosis with a Closed Oroantral Fistula - Jason E. Cohn (Case Reports in Otolaryngology, 2017)
Actinomycosis is a bacterial infection due to Actinomyces israelii, a gram-positive, anaerobic organism that normally affects the cervicofacial region. However, facial injury or trauma (i.e., dental procedures) can allow this bacteria to inhabit other regions. There have been rare reports of actinomycosis of the paranasal sinuses. We present a case of a 50-year-old female who originally presented with a suspected oroantral fistula who subsequently was found to have actinomycosis involving her right maxillary sinus. Additionally, the dental extraction site revealed no connection with the maxillary sinus. We discuss the diagnostic approach and management of this patient as it relates to the limited existing literature.